Distúrbios metabólicos associados à infecção pelo vírus da hepatite C: prevalência em pacientes ambulatoriais seguidos em hospital de referência do Estado do Ceará, Brasil - Oliveira, Ana Paula Pires Lázaro de (2014)
Chronic infection with hepatitis C virus (HCV) is a serious public health problem due to the high cost involved in the treatment of this disease and its complications. Metabolic disorders have been recognized as an important class of extrahepatic manifestations of this virus. HCV is related to the development of insulin resistance (IR) which, in turn, is also associated with a higher degree of hepatic fibrosis, more rapid disease progression and reduction in the rate of sustained virologic. Interferon (INF) is the standard drug for these patients is also associated with the development of other metabolic disorders, especially autoimmune thyroid disease (ATD). The aim of this study was to determine the prevalence of metabolic disorders in a population of patients with and without HCV cirrhosis. A study of quantitative approach, analytical and cross, where 57 patients followed in a referral in hepatology in northeastern Brazil, randomly selected between January and July 2014. For the control group were included 95 volunteers selected randomly with negative HCV serology. Patients underwent medical evaluation, physical examination and collection of blood samples. HOMA-IR was calculated to infer IR. Data were subjected to statistical analysis, being used for this purpose, SPSS version 15.0. In data analysis, bivariate and multivariate analyzes were performed to try to characterize the occurrence of metabolic disorders for the presence of HCV and cirrhosis, with statistical significance level of 5% (p <0.05). A higher frequency of T2DM, IR and hypocholesterolemia among patients with HCV infection compared with the group control (p<0,05). T2DM and IR were also more frequent among individuals with cirrhosis (p <0.05). We observed an increased frequency of obesity and overweight in all groups evaluated. Patients with HCV have high prevalence of ATD, regardless of whether liver fibrosis. Genotype 1 was the most frequently found among individuals diagnosed with metabolic disorders. In conclusion, these data indicate a high prevalence of metabolic disorders among patients with HCV infection in our country and guide it in the context of public health, we must consider the need to develop strategies that promote the reduction of metabolic complications in this susceptible group.